The effects of digital literacy and information literacy on the intention to use digital technologies for learning - A comparative study in Korea and Finland - Moonkyoung Jang; Milla Aavakare; Seongcheol Kim; Shahrokh Nikou (International Telecommunications Society (ITS), 2020)
Digitalisation impacts in the higher education environment and specifically on using digital technologies for learning purposes has increasingly changed such activities. In an informationbased society, where individuals are overloaded with the sheer amount of information and digital tools and devices, literacy skills of an individual play an important role in how activities are being executed. In this paper, we aim to investigate how information and digital literacy of university students impact their decisions to use digital technology for learning. As such, an extension of the UTAUT model is applied on a dataset comprising of 194 and 192 young Korean and Finnish people in their 20s and 30s. Structural Equation Modelling (SEM) results show distinct differences between young Korean and Finnish people in multiple path relationships. For example, while digital literacy has no direct impact on the intention to use technology for learning for Finnish people, this path is significant for the Korean people. Based on this, recommendations for prospect research in adopting the proposed model are outlined and theoretical and practical implications are discussed.
Keywords: 330